Making Processed White Bread Products into Healthy Snacks in the Tahfidzul Qur'an Amanah Middle School Environment - Khairani, Siti; Harahap, Siti Nurlani; Simbolon, Heri Yusuf; Sigalingging, Candra; Sarumaha, Demonius; Lubis, Ruhilah (Talenta Publisher, 2024)
Snacks play an important role in providing energy and other nutritional intake for school-aged children. Children's consumption of snacks is expected to contribute energy and other nutrients that are useful for children's growth. Bread is a food that is popular with people because it has a simple shape, so it is often chosen as a breakfast food before starting daily activities or as a snack to fill the stomach before the actual meal time arrives. Community service activities are carried out at Tahfidzul Qur'an Amanah Middle School in Sei Mencirim, Deli Serdang Regency. The aim is to increase students' understanding of the importance of healthy snacks and the potential dangers of additives contained in processed foods. This activity was carried out on December 7, 2023, including a pre-test to assess students' knowledge about healthy snacks, a comprehensive educational session about the importance of a healthy diet and the dangers of additives, as well as a post-test to evaluate the effectiveness of the intervention. Apart from that, practical demonstrations were carried out on how to turn bread into healthier snacks, especially chocolate rolls. The results of the pre-test and post-test show a significant increase in students' understanding of healthy snacks. The success of this activity shows the potential of similar interventions in promoting health education and better eating habits among school students.